THE PEDAGOGICAL AND METHODOLOGICAL ESSENCE OF THE CONCEPT OF THE NEW NATIONAL EDUCATION PROGRAM - Asadova Ruhsora (International Journal of Literature and Language Studies, 2026)
This article discusses the pedagogical and methodological essence of the concept of the New National Education Program. The New National Education Program is considered an important strategic document aimed at improving the quality of education, modernizing the content of teaching, developing students’ competencies, and introducing innovative pedagogical approaches into the educational process. The article highlights the role of the program in forming learners’ independent thinking, creative abilities, critical analysis skills, communicative competence, and practical application of knowledge. The study also examines the methodological foundations of organizing education on the basis of modern requirements, including competency-based learning, student-centered education, interdisciplinary integration, digital technologies, and assessment mechanisms focused on learning outcomes. It is emphasized that the New National Education Program serves not only to update curricula and textbooks, but also to transform the teacher’s pedagogical activity, improve teaching methods, and ensure the continuity and effectiveness of the educational process. The article substantiates that the successful implementation of this program depends on teachers’ professional competence, methodological preparedness, and ability to apply innovative educational technologies in practice.